2015
DOI: 10.3945/an.115.009415
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nutritional Status and Dietary Patterns on Human Serum C-Reactive Protein and Interleukin-6 Concentrations

Abstract: The inflammatory process plays an important role in the pathogenesis of many chronic diseases, such as cardiovascular diseases, diabetes mellitus type 2, and metabolic syndrome. Serum C-reactive protein (CRP) and interleukin-6 (IL-6) are widely tested inflammatory markers involved in the development of these diseases. Several studies indicate a relation between nutritional status and the concentrations of human high-sensitivity CRP and IL-6. Similarly, the role of diet in reducing inflammation and thereby modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
99
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(106 citation statements)
references
References 52 publications
2
99
3
Order By: Relevance
“…The impact of diet on chronic low-grade inflammation can be reflected by concentrations of inflammatory markers in the bloodstream, including cytokines, acute-phase proteins, soluble adhesion molecules and cytokine receptors [6]. A diet high in red meat, high-fat dairy, refined grains, processed meat, sweets, desserts and sugar-sweetened soft drinks has been associated with higher circulating levels of inflammatory markers in blood samples; whereas a food pattern high in fruits, vegetables and whole grains has been inversely related to inflammatory markers, such as C-reactive protein (CRP) and interleukin-6 (IL-6) [5–10]. Furthermore, a diet rich in fibre and low in fat and sugar was reported to be associated with lower systematic inflammation, which also has been suggested to have a protective role against CVD [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of diet on chronic low-grade inflammation can be reflected by concentrations of inflammatory markers in the bloodstream, including cytokines, acute-phase proteins, soluble adhesion molecules and cytokine receptors [6]. A diet high in red meat, high-fat dairy, refined grains, processed meat, sweets, desserts and sugar-sweetened soft drinks has been associated with higher circulating levels of inflammatory markers in blood samples; whereas a food pattern high in fruits, vegetables and whole grains has been inversely related to inflammatory markers, such as C-reactive protein (CRP) and interleukin-6 (IL-6) [5–10]. Furthermore, a diet rich in fibre and low in fat and sugar was reported to be associated with lower systematic inflammation, which also has been suggested to have a protective role against CVD [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the DASH diet emphasizes the intake of fruits, vegetables, and low-fat dairy intake, as well as legumes, nuts, and emphasizes lower consumption of animal protein, sweets, and sodium. Both diets have been associated with lower plasma levels of inflammatory markers [7]. …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the association between dietary factors and inflammatory markers . For instance, diets high in fruits and vegetables, Mediterranean diet and the Dietary Approaches to Stop Hypertension are inversely associated with serum hs‐CRP levels …”
Section: Introductionmentioning
confidence: 99%
“…11 Several studies have demonstrated the association between dietary factors and inflammatory markers. 12,13 For instance, diets high in fruits and vegetables, Mediterranean diet and the Dietary Approaches to Stop Hypertension are inversely associated with serum hs-CRP levels. 13 Empirically derived dietary patterns have recently emerged in nutritional epidemiology to examine dietdisease associations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation